(untitled) (International Journal of Ayurveda and Pharma Research, 2023)
Marma concept is peculiarity of Ayurveda. These are described as vital points of body featuring articulation of Mansa-Sira-Snayu-Asthi-Sandhi and are associated with severe disability when traumatised. Phana Marma is one of the Urdhwa Jatrugata Marma. According to description from available literature, position of Phana Marma is confined to olfactory epithelium along with olfactory fascicle leading to olfactory bulb present over upper 1/3rd of nasal cavity. Lesion of this region leads to olfactory dysfunction, which is very difficult to treat. Any lesion of epithelium of nasal cavity including respiratory epithelium over lower 2/3rd even leads to olfactory dysfunction. So one should consider this concept of Phana Marma during treatment of any nasal lesion.